The Effectiveness of Hypnobirthing in Reducing Anxiety Level During Delivery - Imannura, Pramita Sandy Ulya; Budhiastuti, Uki Retno; Poncorini, Eti (Journal of Maternal and Child Health, 2016)
Background: Neonatus given birth by pregnant mothers suffering from excessive anxiety and stress have higher risk of low-birthweight, small head circumference, low APGAR score at birth, in adequate neurologyc development, premature birth, weak immunity system, and emotional disorder, than those given birth by happy mothers. This study aimed to examine the effect of effectiveness of hypnobirthing in reducing anxiety level during delivery.Subjects and Method: This was an analytic experimental study with Randomized Control Trial (RCT) design. A sample of 30 pregnant mothers near delivery date was selected for this study and allocated into hypnobirthing group and no-hypnobirthing group. The dependent variable was anxiety during delivery. The independent variable was hypnobirthing. The anxiety level between the two groups was tested by Mann Whitney.Results: After intervention, pregnant mothers who received hypnobirthing had anxiety level as low as 41.33 (p=0.003). Pregnant mothers who did not receive hypnobirthing had anxiety level as low as 51.60 (p=0.003). The reduction of anxiety between the two groups was statistically significant.Conclusion: Hypnobirthing can effectively reduce anxiety among pregnant mothers during birth delivery.Keywords: hypnobirthing, anxietyCorrespondence:ÃÂ Pramita Sandy Ulya Imannura. Masters Program in Public Health, Sebelas Maret University, Surakarta. Email: oxytocinyoga@gmail.com.Journal of Maternal and Child Health (2016), 1(3): 200-204https://doi.org/10.26911/thejmch.2016.01.03.08